ICln: A New Regulator of Non-Erythroid 4.1R Localisation and Function - Bazzini, Claudia; Benedetti, Lorena; Civello, Davide; Zanoni, Chiara; Rossetti, Valeria; Marchesi, Davide; Garavaglia, Maria Lisa; Paulmichl, Markus; Francolini, Maura; Meyer, Giuliano; Rodighiero, Simona (PloS one, 2014)
To optimise the efficiency of cell machinery, cells can use the same protein (often called a hub protein) to participate in different cell functions by simply changing its target molecules. There are large data sets describing protein-protein interactions ("interactome") but they frequently fail to consider the functional significance of the interactions themselves. We studied the interaction between two potential hub proteins, ICln and 4.1R (in the form of its two splicing variants 4.1R80 and 4.1R135), which are involved in such crucial cell functions as proliferation, RNA processing, cytoskeleton organisation and volume regulation. The sub-cellular localisation and role of native and chimeric 4.1R over-expressed proteins in human embryonic kidney (HEK) 293 cells were examined. ICln interacts with both 4.1R80 and 4.1R135 and its over-expression displaces 4.1R from the membrane regions, thus affecting 4.1R interaction with ß-actin. It was found that 4.1R80 and 4.1R135 are differently involved in regulating the swelling activated anion current (ICl,swell) upon hypotonic shock, a condition under which both isoforms are dislocated from the membrane region and thus contribute to ICl,swell current regulation. Both 4.1R isoforms are also differently involved in regulating cell morphology, and ICln counteracts their effects. The findings of this study confirm that 4.1R plays a role in cell volume regulation and cell morphology and indicate that ICln is a new negative regulator of 4.1R functions.